Ergonomic exposure assessments of workplace layout and working postures of sitting and standing workers - Bhuvenesh, Rajamony, Assoc. Prof. (Universiti Malaysia Perlis (UniMAP), 2014)
National Symposium on Advancements in Ergonomics and Safety (ERGOSYM2009), 1st – 2nd December 2009, Perlis, Malaysia